2020
DOI: 10.1111/jpn.13388
|View full text |Cite
|
Sign up to set email alerts
|

The immune adjuvant effect of Astragalus polysaccharide on in ovo injection of Newcastle disease vaccine

Abstract: Newcastle disease (ND), a highly contagious viral infection, can be transmitted between various bird species, is characterized as high mortality and morbidity and accounted for a great loss in poultry industries worldwide; therefore, the OIE-World Organization for Animal Health has classified it as a notifiable disease (Kristina et al., 2012). To date, tremendous efforts have been put into the investigation on curative treatments including oral administration, eye drop, course spray, intranasal instillation an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 45 publications
1
9
0
Order By: Relevance
“…Astragalus polysaccharide significantly downregulated Foxp3+ Treg levels, which correlates with the results of the former studies (Zheng et al, 2020). Previous reports confirmed that astragalus polysaccharide was engaged in the proliferation and polarization of CD4+T cells, thereafter affecting the T cell-mediated immunity (Xue et al, 2020). This effect could be result from Foxp3 suppression.…”
Section: Discussionsupporting
confidence: 87%
“…Astragalus polysaccharide significantly downregulated Foxp3+ Treg levels, which correlates with the results of the former studies (Zheng et al, 2020). Previous reports confirmed that astragalus polysaccharide was engaged in the proliferation and polarization of CD4+T cells, thereafter affecting the T cell-mediated immunity (Xue et al, 2020). This effect could be result from Foxp3 suppression.…”
Section: Discussionsupporting
confidence: 87%
“…Recently, a number of polysaccharides extracted from Chinese medicines have been exploited as adjuvants to boost the efficacies of vaccines (Aygun, 2016; Saki & Salary, 2015). Our previous study revealed that the efficacies of APS as an NDV adjuvant were significantly improved on the humoral and cellular immune responses in chicks via in ovo vaccination (Xue et al, 2020.). Similar to oral treatment, the APS adjuvant was injected into chick embryos at the late stage and entered the embryo's digestive track, where it was assimilated by the chick embryo fed on the amniotic fluid (Uni & Ferket, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that APS relieves reproductive toxicity in phenobarbital-treated epileptic rats by regulating the reproductive hormones [ 26 ]. Administration of live Newcastle disease vaccine with APS in ovo significantly improved the development of chicks and enhanced hatchability and gaining weight [ 27 ]. Thus, APS can prolong the lifespan and enhance hatchability and reproduction in Drosophila .…”
Section: Discussionmentioning
confidence: 99%